Sleep and psychological factors are associated with meeting discharge criteria to return to sport following ACL reconstruction in athletes - Khalladi, K.; Farooq, A.; Sas, B.; Chtourou, H.; Bouras, R.; Racinais, S.; Souissi, S.; Gaoua, N.; Chamari, K.; El Massioui, F. (Biology of Sport, 2021)
This study aimed to determine if sleep quality and psychological factors were associated with time to meet the discharge criteria to return to sport (RTS) following anterior cruciate ligament reconstruction (ACL-R) among athletes. A cohort-study design included 89 athletes following ACL-R. Each participant completed a battery of questionnaires at 6 different time points: within 3 days of injury occurrence and at post-surgery (1.5 m, 3 m, 4.5 m, 6 m and when discharge criteria were met). Assessment included sleep quality and quantity, symptoms of depression, anxiety, stress, psychological readiness to RTS and fear of re-injury. The primary outcome was the time needed to meet all discharge criteria to RTS. Sleep parameters and psychological factors were not associated with time to meet the discharge criteria to RTS. However, athletes that had lower scores of anxiety (OR 1.2 (95% CI 1.0, 1.3) and insomnia (OR 1.2 (95% CI 1.0, 1.3) at baseline were more likely to meet the RTS discharge criteria. Athletes with better sleep quality at 3m, 4.5m and 6m were more likely to meet the RTS discharge criteria OR 1.3 (95% CI 1.1, 1.7), 2.0 (95% CI 1.1-3.4) and 1.4 (95% CI 1.0, 1.9) respectively. Sleep quality and psychological factors were not associated with time to meet the discharge criteria to RTS but impacted whether athletes adhered and completed their rehabilitation program or not. Monitoring sleep quality and psychological factors of athletes before and following ACL-R surgery is important to identify athletes who could have difficulties in adhering to and completing their rehabilitation program to RTS.